Method for preparing high-performance coke powder-based porous carbon adsorbent through flash evaporation Joule heat synergistic activation

Through the flash joule heat synergistic activation method, KMnO4 and carbon black activated coke powder were used to solve the problems of time-consuming and high energy consumption in the traditional process, and high-performance porous carbon was prepared, achieving efficient adsorption and high-value utilization of coke powder.

CN119838582APending Publication Date: 2025-04-18SHANXI UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510051911.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Large-scale storage of coke powder leads to environmental pollution. The traditional activated porous carbon preparation process takes a long time, high energy consumption and limited performance of the resulting materials.

Method used

The flash joule heat synergistic activation method was used, and KMnO4 was used as the oxidation activator and carbon black as the conductive agent to treat the coke powder at instantaneously high temperature to prepare a high-performance coke powder-based porous carbon adsorbent.

Benefits of technology

It has achieved rapid activation and low energy consumption, and prepared porous carbon with high specific surface area and developed pore structure, which has significantly improved the adsorption capacity of organic dyes, reduced the risk of secondary pollution, and achieved high-value utilization of coke powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838582A_ABST
    Figure CN119838582A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a high-performance coke powder-based porous carbon adsorbent through flash evaporation Joule heat synergistic activation, and belongs to the technical field of solid waste resource utilization and porous carbon material preparation. The method comprises the following steps: uniformly mixing coke powder, KMnO4 and carbon black to obtain a mixture; and carrying out flash Joule heat treatment on the mixture to obtain the high-performance coke powder-based porous carbon adsorbent. According to the invention, KMnO4 is used as an efficient oxidation activator, so that the generation quantity and quality of pores are improved; the carbon black improves the conductivity of a coke powder system, so that heat is uniformly released in the flash evaporation process, and the coke powder-based porous carbon with high specific surface area and rich pore structures is obtained through the synergistic effect of the KMnO4 and the carbon black. The method has the advantages of greenness, high efficiency, simplicity and convenience in operation, low energy consumption, excellent performance of the obtained adsorbent and the like, and resource utilization and high-efficiency application of the coke powder are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource utilization and porous carbon material preparation, and in particular to a method for preparing a high-performance coke powder-based porous carbon adsorbent through synergistic activation with flash Joule heat. Background Art

[0002] With the in-depth development of industrialization, the coal coking process plays an important role in energy supply and steel production. However, a large amount of coke powder (also known as coke powder or undersize) in the form of fine particles will be produced during the coking process, and its annual output is very huge. According to relevant statistics, the amount of coke powder produced in the world each year can reach more than hundreds of millions of tons, of which only a small part is used as fuel or filler, and most of the coke powder is stored or discarded, resulting in waste of resources and environmental pollution. During the long-term stacking process, coke powder is easily affected by natural factors such as wind and rain to form dust or exudate, causing potential pollution to the soil and water bodies; in addition, coke powder also has certain flammability and toxicity, and if it is not managed properly, it will bring fire or explosion hazards. Therefore, how to achieve high-value or large-scale reuse of coke powder has always been a difficult problem that needs to be solved urgently in the field of energy and environment.

[0003] At the same time, porous carbon materials are widely used in adsorption, catalysis, energy storage and other fields due to their large specific surface area, rich pore structure and stable chemical properties, including sewage treatment, waste gas purification and electrochemical energy storage (such as supercapacitors and battery electrode materials). The traditional methods for preparing porous carbon mainly include:

[0004] 1. Physical activation method: Usually, water vapor or carbon dioxide is introduced at high temperature (700-1000°C) to etch the carbon material. The preparation process has high energy consumption and strict equipment requirements;

[0005] 2. Chemical activation method: After impregnating the carbon precursor with reagents such as KOH, ZnCl2, H3PO4, etc., carbonization activation is performed at medium and high temperatures; although the reaction temperature is relatively low, the washing steps are cumbersome and may cause secondary pollution;

[0006] 3. Template method: The carbon precursor structure is limited by a hard template (SiO2, montmorillonite) or a soft template (surfactant, etc.) to obtain porous carbon with controllable pore distribution, but the template preparation and removal steps are complicated and costly;

[0007] 4. Hydrothermal method: Hydrothermal carbonization of biomass or other carbon sources in a high-temperature autoclave, followed by a carbonization activation step to obtain a higher specific surface area;

[0008] 5. Microwave method: Relying on microwaves to quickly heat the carbon source and assisting chemical activators to achieve pore generation, but it has high requirements on equipment, limited microwave penetration depth, and is prone to uneven heating of the material.

[0009] In the above method, waste coke powder is used as a carbon source to prepare porous carbon. Some studies and patents have attempted to apply traditional chemical activation or physical activation to coke powder, but they still face the following prominent problems: (1) The coke powder has a complex composition, high ash and impurity content, and traditional homogeneous heating is difficult; (2) It requires a long period of high-temperature treatment, and the process steps are cumbersome and energy-intensive; (3) The pore structure of the obtained porous carbon is not well developed, and the performance needs to be improved. Summary of the invention

[0010] In view of the outstanding problems in the prior art such as large-scale storage of coke powder causing environmental pollution, the traditional activation process for preparing porous carbon taking a long time, high energy consumption and limited performance of the obtained material, the purpose of the present invention is to provide a method for preparing high-performance coke powder-based porous carbon adsorbent by flash Joule heat synergistic activation. The present invention uses KMnO4 as a highly efficient oxidation activator to increase the quantity and quality of pore generation; carbon black improves the conductivity of the coke powder system, so that the flash process releases heat evenly, and through the synergistic effect of KMnO4 and carbon black, a coke powder-based porous carbon with high specific surface area and rich pore structure is obtained.

[0011] In order to achieve the above object, the present invention provides the following technical solutions:

[0012] One of the technical solutions of the present invention is a method for preparing a high-performance coke powder-based porous carbon adsorbent by flash Joule heat synergistic activation, comprising the following steps:

[0013] The coke powder, KMnO4 and carbon black are uniformly mixed to obtain a mixture;

[0014] The mixed material is subjected to flash Joule heat treatment to obtain a high-performance coke powder-based porous carbon adsorbent.

[0015] The second technical solution of the present invention is a high-performance coke powder-based porous carbon adsorbent prepared by the above method.

[0016] A third technical solution of the present invention is an application of the above-mentioned high-performance coke powder-based porous carbon adsorbent in adsorbing organic dyes in water.

[0017] The present invention discloses the following technical effects:

[0018] (1) Rapid activation and low energy consumption: Traditional activation methods often require several hours of high-temperature calcination. The flash Joule heat of the present invention only requires a discharge process of milliseconds to seconds to complete the activation and carbonization of the coke powder, greatly reducing the preparation cycle and energy consumption.

[0019] (2) Excellent material structure: Through the synergistic effect of KMnO4 activation and carbon black conductive agent, the porous carbon of the present invention has a developed pore network and a BET specific surface area of ​​100 to 200 m 2 / g (or even higher), and the adsorption capacity for macromolecular pollutants such as organic dyes is significantly enhanced.

[0020] (3) High-efficiency pollutant removal: Under the same adsorption conditions, the porous carbon prepared by the present invention can achieve a removal rate of more than 99.9% for typical organic dyes (methylene blue, rhodamine B); the adsorption equilibrium time is shortened to less than 60 minutes, which is far superior to some traditional activated carbon or porous carbon materials.

[0021] (4) Green and environmentally friendly, resource recycling: The present invention uses industrial waste coke powder as raw material and combines it with a simple flash Joule heat process, which reduces the consumption of a large amount of chemical reagents and water resources, effectively reduces the risk of secondary pollution, and realizes the high-value utilization of coke powder.

[0022] (5) Easy operation and industrialization: The equipment required for the present invention includes a conventional grinding and mixing device and a flash discharge device, which does not require lengthy pretreatment or subsequent washing. The process is simple and easy to promote on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is the SEM image of the HPC-X prepared in Example 1;

[0025] Figure 2 The adsorption isotherm curve (a) of HPC-X and the pore size distribution curve (b) of HPC-X prepared in Example 1;

[0026] Figure 3 FTIR graph of HPC-X prepared in Example 1;

[0027] Figure 4 The adsorption capacity and removal rate of methylene blue adsorbed by HPC-X prepared in Example 1 at 25°C are trend charts;

[0028] Figure 5 This is a graph showing the adsorption capacity and removal rate of Rhodamine B by the HPC-X prepared in Example 1 at 25°C. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] Flash Joule Heating technology is based on the principle of heat release from the resistivity of carbon materials. It uses instantaneous high current discharge to rapidly heat the material to a high temperature in a very short time (usually milliseconds to seconds), and quickly cools it after the discharge. By precisely controlling the process parameters of Flash Joule Heating, a specific material structure and properties are formed. Currently, there is a lack of in-depth coupling design of the electrical characteristics of coke powder and the instantaneous heating mechanism for the resource utilization of coke powder, an industrial by-product, especially in the synergistic effect of KMnO4 activation and carbon black conductivity enhancement.

[0035] A first aspect of the present invention provides a method for preparing a high-performance coke powder-based porous carbon adsorbent by flash Joule heat synergistic activation, comprising the following steps:

[0036] The coke powder, KMnO4 and carbon black are uniformly mixed to obtain a mixture;

[0037] The mixed material is subjected to flash Joule heat treatment to obtain a high-performance coke powder-based porous carbon adsorbent.

[0038] The present invention significantly promotes pore formation and improves reaction efficiency during subsequent rapid heating by adding specific activators and conductive agents to the carbon precursor. The activator selected by the present invention is KMnO4, and the conductive agent is carbon black. As an activator with strong oxidizing properties, KMnO4 can produce a large amount of oxidizing intermediates at instantaneous high temperature, corrode the carbon skeleton of the coke powder and generate abundant pores; and carbon black has good conductivity. Adding a small amount of carbon black can make the current distribution inside the mixture more uniform, avoid local overheating or sintering, and make the instantaneous discharge more uniform. The present invention synergistically combines the rapid heating and cooling characteristics of flash Joule heat to greatly improve the specific surface area and pore structure perfection of porous carbon.

[0039] Compared with common activators (KOH, ZnCl2, etc.), KMnO4 aqueous solution is relatively mild in nature and can avoid the corrosion and subsequent washing burden caused by the use of strong alkali or chloride salts. In addition, potassium permanganate also has certain template and catalytic effects, which helps to form a unique pore structure (mesopores and macropores, directional regulation of pore structure), which is more conducive to the adsorption of macromolecular substances / dye substances; compared with other conductive additives (graphite powder, carbon nanotubes, etc.), carbon black is relatively cheap and easy to disperse, and good conductivity can be obtained by adding less. Carbon black can also point-to-point contact with carbon precursors, which is beneficial to improve the adsorption performance of the adsorbent. Therefore, for the preparation of porous carbon with coke powder as the main raw material, "KMnO4+carbon black+flash Joule heat" has the potential to quickly obtain high specific surface area and rich pore structure at low energy consumption.

[0040] In some embodiments of the present invention, before the coke powder, KMnO4 and carbon black are uniformly mixed, the step of grinding the coke powder and passing it through a 100-mesh sieve is also included.

[0041] The present invention does not specifically limit the method for uniformly mixing coke powder, KMnO4 and carbon black, and conventional technical means of those skilled in the art can be used, such as ball milling or planetary mixer. The present invention further improves the uniform heating effect of the precursor material during the flash evaporation process by uniformly mixing coke powder, KMnO4 and carbon black.

[0042] In some embodiments of the present invention, the mass ratio of the coke powder to KMnO4 is 1:(0.1-5); the doping amount of carbon black is 4wt%-5wt% of the total mass of the coke powder and KMnO4.

[0043] In some embodiments of the present invention, the mass ratio of the coke powder to KMnO4 is 1:(0.1-3); the doping amount of carbon black is 4.5wt%-5wt% of the total mass of the coke powder and KMnO4.

[0044] In some embodiments of the present invention, the mass ratio of the coke powder to KMnO4 is 1:(0.1-0.5); the doping amount of carbon black is 5wt% of the mixture of coke powder and KMnO4.

[0045] The present invention adjusts the ratio of coke powder to KMnO4 to obtain a higher specific surface area and a more uniform pore structure. When the ratio of coke powder to KMnO4 is not within the above range, the specific surface area of ​​the prepared porous carbon will decrease and the adsorption efficiency will be reduced.

[0046] In some embodiments of the present invention, before subjecting the mixture to the flash Joule heat treatment, a step of measuring the resistance of the mixture is further included, and the flash Joule heat treatment is performed when the resistance of the mixture is ≤6Ω.

[0047] The present invention puts the mixed material into a high temperature resistant container, compacts it and measures the resistance. According to the resistance and tightness of the sample, the carbon black doping amount or the compaction strength is properly adjusted to make the resistance below 6Ω to ensure uniform conduction during flash discharge.

[0048] In some embodiments of the present invention, the parameters of the flash Joule heat treatment are set as follows: discharge voltage 100-300V, single discharge time 1s, total discharge 1-10s, and flash times 1-10 times.

[0049] In some embodiments of the present invention, the parameters of the flash Joule heat treatment are set as follows: discharge voltage 100-300V, single discharge time 1s, total discharge 1-5s, and flash evaporation times 1-5 times.

[0050] In the present invention, if the number of discharges and flash evaporations is too large, the porous carbon pores will collapse, the specific surface area will decrease, and the adsorption performance will be reduced.

[0051] When the above-mentioned flash Joule heat treatment is implemented, the maximum temperature of the flash Joule heat process is between 1000 and 3500°C.

[0052] The second aspect of the present invention provides a high-performance coke powder-based porous carbon adsorbent prepared by the above method. The porous carbon adsorbent prepared by the present invention has a specific surface area of ​​≥100m 2 / g, and its pore structure is mainly mesopores and contains a moderate amount of micropores.

[0053] A third aspect of the present invention provides a use of the above-mentioned high-performance coke powder-based porous carbon adsorbent in adsorbing organic dyes in water.

[0054] In some embodiments of the present invention, the organic dye is methylene blue or rhodamine B.

[0055] In some embodiments of the present invention, the dosage of the high-performance coke powder-based porous carbon adsorbent is 0.5-1.5 mg / mL, preferably 1 mg / mL.

[0056] The porous carbon adsorbent prepared by the invention has a removal efficiency of ≥99.9% for typical dyes such as methylene blue or rhodamine B, and can reach adsorption equilibrium within 60 minutes.

[0057] The porous carbon adsorbent prepared by the invention has the function of specific adsorption to methylene blue and rhodamine B.

[0058] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0059] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0060] Example 1

[0061] A high-performance coke powder-based porous carbon adsorbent, the preparation steps are as follows:

[0062] The coke powder was ground and passed through a 100-mesh sieve, and then 5 g of coke powder, 0.5 g of KMnO4 and 0.275 g of carbon black were weighed and mixed evenly to obtain a mixture, which was then placed in a quartz tube. First, a graphite electrode is inserted into one end of the quartz tube, and then 100 mg of the mixture is added into the quartz tube, and then another graphite electrode is inserted from the other end to compact the sample, and then the quartz tube is placed on a flash Joule heating device to detect the resistance of the sample. By appropriately adjusting the knob of the flash Joule heating device, the compression degree of the sample is adjusted, the compression rate of the sample is changed, and the resistance is adjusted until the resistance is ≤ 6Ω. After that, the sample is discharged 3 times under the flash voltage and flashed once. The single discharge time is 1s, and the maximum temperature generated by Joule heat is 2998°C to obtain porous carbon; wherein the flash voltages are 100V, 140V, 180V, and 220V, respectively, and the prepared porous carbon is named HPC-X, wherein X is the flash voltage (X=100V, 140V, 180V, 220V).

[0063] Comparative Example 1

[0064] The preparation method of the porous carbon adsorbent provided in this comparative example is the same as that of Example 1, except that the addition of KMnO4 is omitted. The obtained porous carbon is named HPC-1.

[0065] Comparative Example 2

[0066] The preparation method of the porous carbon adsorbent provided in this comparative example is the same as that of Example 1, except that the addition of carbon black is omitted. The obtained porous carbon is named HPC-2.

[0067] The pore structure parameters of the porous carbon prepared in Example 1 and Comparative Examples 1-2 are shown in Table 1.

[0068] Table 1 Pore structure parameters of porous carbon

[0069]

[0070] The BET diagram of the porous carbon prepared in Example 1 is shown in Figure 2 , where (a) is the adsorption isotherm curve of HPC-X, and (b) is the pore size distribution curve of HPC-X. Figure 2 It can be seen that according to the classification of IUPAC adsorption isotherms, all porous carbons conform to type IV adsorption-desorption isotherms, and the pore structure is mainly composed of mesopores.

[0071] The FTIR image of the porous carbon prepared in Example 1 is shown in Figure 3 ,from Figure 3 It can be seen that the positions of stretching vibrations of functional groups in different HPC-X are basically the same, but the intensity varies with the change of flash voltage. The main functional groups in porous carbon are -OH, C=C, -CH3, CO and CH.

[0072] Performance Evaluation

[0073] 1. The porous carbon prepared in Example 1 and Comparative Examples 1-2 was used to adsorb methylene blue in water. The experimental conditions were: the volume of simulated methylene blue wastewater was 20 mL, the concentration of methylene blue was 500 mg / mL, the temperature was 25°C, the dosage of porous carbon was 20 mg, the oscillation frequency was 150 r / min, the time was 24 h, and the pH was 7. The calculation formulas for adsorption capacity (q) and removal rate (R) are shown in (1) and (2):

[0074]

[0075] Where, m is the mass of porous carbon HPC-X (g); C0 is the initial concentration of methylene blue solution (mg / L); C e is the residual concentration of methylene blue solution after adsorption equilibrium (mg / L).

[0076] Table 2 Adsorption capacity of methylene blue on porous carbon

[0077]

[0078] 2. The porous carbon prepared in Example 1 and Comparative Examples 1-2 was used to adsorb Rhodamine B in water. The experimental conditions were: the volume of simulated Rhodamine B wastewater was 20 mL, the concentration of Rhodamine B was 500 mg / mL, the temperature was 25°C, the dosage of porous carbon was 20 mg, the oscillation frequency was 150 r / min, the time was 24 h, and the pH was 7. The calculation formulas for adsorption capacity (q) and removal rate (R) are shown in (3) and (4):

[0079]

[0080]

[0081] Where, m is the mass of porous carbon (g); C0 is the initial concentration of Rhodamine B solution (mg / L); C e is the residual concentration of Rhodamine B solution after adsorption equilibrium (mg / L).

[0082] Table 3 Adsorption capacity of Rhodamine B on porous carbon

[0083]

[0084] 3. The porous carbon prepared in Example 1 was used to adsorb Cr(VI) in water. The experimental conditions were: the volume of simulated chromium-containing wastewater was 20 mL, the concentration of Cr(VI) was 100 mg / mL, the temperature was 25°C, the dosage of porous carbon was 20 mg, the oscillation frequency was 150 r / min, the time was 24 h, and the pH was 7. The calculation formula for the adsorption capacity (q) was the same as above.

[0085] Table 4 Adsorption capacity of porous carbon for Cr(VI)

[0086]

[0087] The principles and implementation methods of the present invention are described in this article using implementation cases. The above examples are only used to help understand the core methods and core ideas of the present invention. The implementation cases described above are preferred implementation methods of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, it should be pointed out that various modifications and variations of the present invention are possible for those skilled in the art.

[0088] Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention, or direct application of the concept and technical solution of the invention to other occasions without improvement, shall be deemed to be within the protection scope of the present invention.

Claims

1. A method for preparing a high-performance coke powder-based porous carbon adsorbent by flash Joule heat synergistic activation, characterized in that: The following steps are involved: The coke powder, KMnO4 and carbon black are uniformly mixed to obtain a mixture; The mixed material is subjected to flash Joule heat treatment to obtain a high-performance coke powder-based porous carbon adsorbent.

2. The method for preparing high-performance coke powder-based porous carbon adsorbent by synergistic activation of flash Joule heat according to claim 1, characterized in that: Before the coke powder, KMnO4 and carbon black are uniformly mixed, the process also includes grinding the coke powder and passing it through a 100-mesh sieve.

3. The method for preparing high-performance coke powder-based porous carbon adsorbent by synergistic activation of flash Joule heat according to claim 1, characterized in that: The mass ratio of the coke powder to KMnO4 is 1:(0.1-5); the doping amount of carbon black is 4wt%-5wt% of the total mass of the coke powder and KMnO4.

4. The method for preparing high-performance coke powder-based porous carbon adsorbent by synergistic activation of flash Joule heat according to claim 1, characterized in that: Before subjecting the mixture to flash Joule heat treatment, the method further includes a step of measuring the resistance of the mixture, and when the resistance of the mixture is ≤6Ω, the flash Joule heat treatment is performed.

5. The method for preparing high-performance coke powder-based porous carbon adsorbent by synergistic activation of flash Joule heat according to claim 1, characterized in that: The parameters of the flash Joule heat treatment are set as follows: discharge voltage 100-300V, single discharge time 1s, total discharge 1-10s, and flash times 1-10 times.

6. A high-performance coke powder-based porous carbon adsorbent prepared according to the method according to any one of claims 1 to 5.

7. Use of the high-performance coke powder-based porous carbon adsorbent according to claim 6 in adsorbing organic dyes in water.

8. The use of the high-performance coke powder-based porous carbon adsorbent in adsorbing organic pollutants in water according to claim 7, characterized in that: The organic dye is methylene blue or rhodamine B.

9. The use of the high-performance coke powder-based porous carbon adsorbent in adsorbing organic pollutants in water according to claim 7, characterized in that: The dosage of the high-performance coke powder-based porous carbon adsorbent is 0.5-1.5 mg / mL.

Citation Information

Cited By

  • A multiphase silicate material, its preparation and use

    CN122499750A